2018
DOI: 10.1051/0004-6361/201833617
|View full text |Cite
|
Sign up to set email alerts
|

Photometric redshifts from SDSS images using a convolutional neural network

Abstract: We developed a Deep Convolutional Neural Network (CNN), used as a classifier, to estimate photometric redshifts and associated probability distribution functions (PDF) for galaxies in the Main Galaxy Sample of the Sloan Digital Sky Survey at z < 0.4. Our method exploits all the information present in the images without any feature extraction. The input data consist of 64×64 pixel ugriz images centered on the spectroscopic targets, plus the galactic reddening value on the line-of-sight. For training sets of 100… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
185
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 45 publications
(42 reference statements)
5
185
0
1
Order By: Relevance
“…Future large-field photometric surveys, such as Euclid (Laureijs et al 2011), HSC (Aihara et al 2018) and LSST (LSST Dark Energy Science Collaboration 2012) will be able to confirm and extend these results by probing a wider group mass range and a larger variety of environment (though in 2D) while relying on state-of-the art photometric redshift extraction techniques (e.g. Davidzon et al 2019;Pasquet et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Future large-field photometric surveys, such as Euclid (Laureijs et al 2011), HSC (Aihara et al 2018) and LSST (LSST Dark Energy Science Collaboration 2012) will be able to confirm and extend these results by probing a wider group mass range and a larger variety of environment (though in 2D) while relying on state-of-the art photometric redshift extraction techniques (e.g. Davidzon et al 2019;Pasquet et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…While ML methods such as ANN have been used for almost 30 years [226], more recent works focus on CNNs, due to their ability to process and analyze images in a relatively computationally efficient way. CNNs have been used to understand the morphology of galaxies [227][228][229], predict photometric redshifts [230,231], detect galaxy clusters [232], identify gravitational lenses [233][234][235][236] and reconstruction of images [237] Video classification is yet another field that keeps improving along with advances in ML. Karpathy et al [238] have used CNNs to classify sports-related videos found on YouTube into their corresponding sports.…”
Section: Machine Learning In Data-mining and Processingmentioning
confidence: 99%
“…The most likely sources for the human classifications for training are citizen science efforts such as Galaxy Zoo or efforts involving the classification of more restricted datasets by professional astronomers 69 . The promise and efficiency of deep learning and other machine learning techniques lend themselves to other applications, such as photometric redshift determinations [178][179][180] or more even basic steps in the photometric pipeline such as object identification, deblending and segmentation. 62,63 .…”
Section: Machine Learningmentioning
confidence: 99%